From Local Wisdom to Independent Tourism Villages : Analysis in the Perspective of Local Economic Empowerment - Cherly Wangkay; Eny Haryati; Amirul Mustofa (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study analyzes the potential of local wisdom in the development of tourism villages in Indonesia, with a focus on local economic empowerment. Local wisdom, which includes traditions, culture, art, and social systems, is often not documented or utilized to its full potential in the tourism sector. Through a qualitative approach, this study explores how local wisdom can be used as the main attraction in the development of independent and sustainable tourism villages. Several tourist villages that have managed local wisdom effectively, such as Osing Village and Reog Village, are used as examples in this study. The findings show that although many villages have great cultural potential, many have not yet utilized digital technology in promoting their local wisdom. Better documentation and the use of technology such as digital platforms can increase the visibility of tourist villages and expand the market. In addition, local economic empowerment is achieved through the management of local wisdom that involves the community in all development processes. This study provides recommendations for strategies to optimize the utilization of local wisdom, including increased documentation, community involvement, and the use of digital technology, to create highly competitive tourist villages and make a real contribution to local economic empowerment.